Inward Investment and Technical Progress in the UK Manufacturing Sector - Hubert, Florence (OECD Publishing, 2000)
This paper investigates the impact of direct investment by foreign-owned companies on technical progress and hence labour productivity in the UK manufacturing sector. Using an industry-level panel data set we find that foreign-owned firms have a significant positive effect on the level of technical efficiency in domestic firms. There is evidence of significant intra-industry and inter-industry spillovers from inward investment. These findings remain robust even when other factors such as imports and domestic R&D expenditures are allowed for. Inward investment appears to be a much more important source of technical progress than foreign trade ...
Keywords: Economics; United Kingdom